An Analysis of Non-Traditional Activities at German Savings Banks~– Does the Type of Fee and Commission Income Matter? - Matthias Köhler (Credit and Capital Markets – Kredit und Kapital, 2019)
In this paper, we use a fully anonymized dataset provided by the German Savings Banks Association (DSGV) to analyse which savings banks have expanded into fee-producing activities more quickly. In addition, we investigate whether their profitability and stability is correlated with the share of their fee and commission income. Notably, we examine whether the effect on bank profitability differs depending on the type of fee and commission income. Our results support the view that savings banks with low net interest margins are under greater pressure to expand into fee-producing activities. They further suggest that savings banks with a higher share of fee and commission income, in particular from payment services and securities business, also have a higher profitability. The Z-score also correlates positively with the share of securities business income, possibly because it responds to different shocks than net interest income and, therefore, offers a large diversification potential. – – In diesem Paper verwenden wir einen vollständig anonymisierten Datensatz des Deutschen Sparkassen- und Giroverbands (DSGV), um zu untersuchen, welche Sparkassen ihr Provisionsgeschäft schneller ausgebaut haben. Außerdem analysieren wir, wie stark die Profitabilität und Stabilität dieser Banken mit dem Anteil des Provisionseinkommens am gesamten operativen Einkommen korreliert sind. Zu beachten ist, dass wir dabei nach der Art des Provisionseinkommens unterscheiden. Unsere Ergebnisse stützen die Hypothese, dass Sparkassen mit einer hohen Zinsmarge unter geringerem Druck stehen, ihr Provisionsgeschäft auszubauen. Sie lassen ferner darauf schließen, dass Sparkassen mit einem Anteil an Provisionseinkommen aus dem Zahlungsverkehr und dem Wertpapiergeschäft eine höhere Profitabilität haben. Der Z-Score korreliert ebenfalls positiv mit dem Anteil an Provisionseinkommen aus dem Wertpapiergeschäft, möglicherweise weil es anderen Schocks ausgesetzt ist als das Zinseinkommen und deshalb ein großes Diversifikationspotential birgt.
Keywords: G20; G21; G29; 330; Savings Banks; Fee and Commission income; Profitability